Development of guided inquiry based modules to improve learning outcomes and metacognition skills of student - Intan Pratiwi; Ismanisa Ismanisa; Asep Wahyu Nugraha (Jurnal Pendidikan Kimia (JPKim), 2019)
This study aims to find out the guided inquiry-based acid-base module that have been developed meets the criteria of the National Education Standards Agency (BSNP); learning outcomes increase after being taught using guided inquiry based modules; there is a relationship between student learning outcomes with student metacognition skills. The population was all students of class XI Senior High School Education Foundation Mulia Medan Academic. Class XI Science was chosen as the sample determined by simple random sampling. The research method used is the development research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The research instrument was a learning outcome test, a metacognitive questionnaire taken from the Metacognitive Awareness Inventory (MAI) instrument, and a validation sheets. Data analysis was conducted using descriptive analysis, feasibility analysis, the results of the metacognitive questionnaire, and the results of learning tests. The hypothesis test using the t-test and assisted with the SPSS 19.0. The results of the study showed that the modules were developed according to the criteria of the National Education Standards Agency (BSNP)obtained: content = 3.85; language = 3.89; presentation = 3.83; graphic = 3.87 with valid criteria;tcount is greater than ttable (8.321> 1.708) shows that student chemistry learning outcomes increase after being taught using guided inquiry-based modules; the results of the correlation obtained rcount>rtable(0.472 > 0.388) showed that there is a relationship between metacognition skills and chemistry learning outcomes of students.Keywords:Development research; learning outcomes;guided inquiry; metacognition skills; module